The relationship between lameness prevalence and pasture access in 659 dairy herds in Germany. - Anna Tillack; Roswitha Merle; Kerstin-Elisabeth Müller; Martina Hoedemaker; Katharina Charlotte Jensen; Alexander Bartel; Andreas W Oehm; Marcus Klawitter; Annegret Stock (PLoS ONE, 2024)
Lameness in dairy cows is an expression of pain most likely originating from a claw disorder, causing impaired animal wellbeing and substantial economic losses for farmers. The aim of this study was to investigate the effects of access to pasture, time spent on pasture, and season on farm level lameness prevalence. The survey was part of a cross-sectional observational study, in which farms in three regions of Germany (North, East and South) were visited by study veterinarians. On each farm (total: 659, N: 240, E: 247, S: 172), management data were recorded, and cows were scored for locomotion, according to Sprecher. Median farm-level lameness prevalence (Score 3/5 or higher) was 29.4% (IQR: 18.7% - 42.0%), and 8.2% (IQR: 3.7% - 14.0%) for severe lameness (Score 4/5 or higher). Farm-level lameness prevalence continuously decreased with increasing time spent on pasture (up to approximately 10 hours per cow per day). On farms that did not offer their cows access to pasture lameness prevalence did not show a seasonal variation. On farms where cows had pasture access for up to three hours per day lameness prevalence peaked in autumn. In contrast, on farms offering their cows access to pasture beyond three hours per day the peak of lameness was observed in spring. Our results revealed that even short periods of pasture access of at least two hours per cow and day (on average per year) are beneficial for the locomotion of dairy cows.